Synthesis, structural characterization and biological activities of Ag(I) complexes with mixed ligands of thiosemicarbazone and triphenylphosphine. / Nur Adila Fatin Mohd Khir - Nur Adila Fatin , Mohd Khir (2019)
Six Ag(I) complexes containing mixed ligand of thiosemicarbazone derivatives and triphenylphosphine were synthesized. The structural information of the ligands and its silver complexes were assembled using various spectroscopic techniques such as CHN elemental analysis, Fourier Transformed Infrared (FTIR), 1H, 13C, 31P{1H}and 2D-NMR. The spectroscopic data suggested that the 4-phenyl-3-thiosemicarbazone ligands were bound to the silver centre via the neutral sulfur donor atom. The complexes were known to be in tetrahedral arrangement with the thiosemicarbazone moiety existed as a thione tautomer. The biological properties of the complexes were investigated for their antiplasmodial and antiproliferative activities. The in vitro antiproliferative activities of these complexes were investigated towards the MDA-MB-231 and MCF-7 breast cancer cell line as well as HT-29 colon cancer cell line, yielding IC50 values in the moderate micromolar range for all the cell lines. These complexes were also tested for their antiplasmodial activity against chloroquine resistant P. falciparum parasite; HRP2 assay, along with cytotoxicity test on MDBK cells and possess good to modest activity.